Multimodal imaging in the assessment of quadricuspid aortic valve - Michele D’Alonzo; Antonino Massimiliano Grande; Ivan Casale; Antonio Fiore (Journal of Cardiothoracic Surgery)
Abstract Quadricuspid aortic valve (QAV) is a rare congenital anomaly of the aortic valve, with an incidence of 0.05-0.1%, often associated with aortic regurgitation. The condition typically presents between the ages of 46 and 50, with a slight male predominance. While diagnosis is generally made via transthoracic echocardiography (TTE), this method can occasionally fail to identify QAV, necessitating the use of transoesophageal echocardiography and cardiac computed tomography for more accurate assessment of valve morphology. We present the case of a 57-year-old male who experienced chest pain for three months. Although TTE revealed severe aortic regurgitation, it did not detect the QAV. The anomaly was ultimately identified through advanced imaging techniques prior to surgery, which confirmed the presence of this rare aortic valve morphology.